MAKNA SALIB BAGI KEHIDUPAN MANUSIA MELALUI LENSA TEOLOGI PAULUS DALAM SURAT 1 KORINTUS - Gulo, Refamati (STT-RAI Batam, 2024)
The cross is a central symbol in Christian theology that contains fundamental meaning. The meaning of the cross in the letters of the Apostle Paul has strong doctrinal and historical substance. Letter 1 Corinthians is the main focus, in this study. Paul faced various issues and conflicts in the Corinthian church, responding by referring to the meaning of the cross as the center of his teaching. For Paul, the meaning of the cross was profound; through the cross, God revealed His love to redeem His people from their sins. This study aims to deeply explore Paul's thoughts on the meaning of the cross, how his views provide significant theological insights for human life. The method used is qualitative with a thematic analysis approach. The author of Paul's thoughts on the cross is based on textual searches and hermeneutical patterns. The results show that the cross provides a way of redemption, forgiveness, salvation, justification, becomes the center of solutions to various conflicts, and human problems. This research also contributes to the understanding and development of spirituality in the context of modern life where Christians can realize sincere love for others.